The Role of Artificial Intelligence in Supporting Effective and Adaptive Learning Planning - Ni Made Yeni Suranti; Ni Ketut Yeni Pradmawati (Indonesian Journal of Innovation and Educational Technology, 2026)
The development of digital technology is driving the use of Artificial Intelligence (AI) in education, particularly in lesson planning. This article aims to examine the role of Artificial Intelligence in supporting effective and adaptive lesson planning. The method used is a literature review, reviewing various books, journal articles, and relevant scientific proceedings. The results of the study indicate that AI, particularly generative Artificial Intelligence such as ChatGPT, can help teachers develop lesson plans that are more structured, aligned, and based on student needs. AI supports the formulation of learning objectives, the selection of learning strategies, the development of learning activities, and the design of assessments that align with learning outcomes. In addition to increasing effectiveness, AI also plays a role in creating adaptive lesson plans through the analysis of data on student abilities and learning progress. However, the use of AI still faces challenges related to teacher digital literacy, ethics, data privacy, and infrastructure readiness. Therefore, AI needs to be used wisely as a tool to support teacher professionalism.